Exploring the importance and preference of sugar feeding behaviour of malaria vectors in sugar plantations of southern Malawi - Kennedy Zembere; Sylvester Coleman; James Chirombo; Rex Mbewe; Julie-Anne Tangena (PLoS ONE, 2026)
Background Reliable tools are needed to control opportunistic outdoor biting and resting malaria vectors that remain beyond the reach of indoor targeted interventions. The attractive targeted sugar baits (ATSBs) have demonstrated effectiveness in some settings but have shown limited impact in other areas, in part due to differences in mosquito species’ preferences and the presence of competing natural sugar sources. We evaluated the sugar-feeding preferences of Anopheles gambiae in Chikwawa, southern Malawi, to inform context specific sugar-based vector control interventions. Methods Using three collection tools, CDC Light traps; Prokopack aspirator and the barrier screen, we collected 187 adult anophelines from the Illovo sugar plantations. Collected mosquitoes were subjected to cold anthrone tests in the laboratory to assess the presence of plant sugars in their gut. Additionally, 810 adult Anopheles gambiae s.l., reared in the insectary from wild caught larvae, were exposed in an olfactory-driven choice experiment to identify the most attractive available sugar source in the area. Sugar sources included guavas, melon, bananas, mango, marula and sugarcane. Results Over 40% (n = 74) of the collected Anopheles mosquitoes- including An. gambiae s.l., An. funestus , An. coustani and An. tenebrous were found to have fed on natural sugar sources. For the sugar attractiveness tests for An. gambiae s.l., guava was found to be twice as attractive (IRR = 1.97, 95% CI: 1.49–2.62, p < 0.001) as sugarcane (our reference fruit), followed by banana (IRR = 1.68, 95% CI: 1.26–2.24, P < 0.001), then mango, and melon (IRR = 1.49, 95% CI: 1.11–2.01, P = 0.008) and (IRR = 1.45, 95% CI: 1.08–1.96, P = 0.014) respectively. Conclusion Sugar feeding is a key activity for Anopheles mosquitoes and presents a potential target for control. Understanding local sugar source preferences will help tailor novel mosquito control intervention strategies such as the ATSBs to specific ecological contexts.